Physical function, daily activities, and spinal pain in the elderly: A cross-sectional study - Paulina Kowalewska; Małgorzata Wójcik; Aleksandra Banaszak; Kacper Bernatowicz; Mateusz Motyl; Patrycja Wołodźko; Matylda Sauermann; Maciej Wołczek; Eryk Pietruszak; Bartosz Aniśko (PLoS ONE, 2026)
Population aging is associated with progressive functional decline and a rising prevalence of chronic spinal pain, representing a major challenge for public health and geriatric care. Objective To evaluate the relationships between spinal pain, functional mobility, balance, and physical activity level in older adults. Methods A total of 28 community-dwelling seniors (25 women, 3 men; mean age 70.8 ± 5.1 years) participated in the study. Functional mobility was assessed using the Timed Up and Go (TUG) test and reaction time. Postural balance was measured using a force platform. Disability was evaluated with NDI and ODI, and physical activity with IPAQ. Results Significant correlations were found between age and TUG (r = 0.61, p < 0.001), and between Neck Disability Index (NDI) and postural sway area (r = 0.45, p = 0.016). No significant relationship was observed between pain and physical activity levels. Conclusion Spinal pain and age are significantly associated with functional decline and impaired balance in older adults. These findings suggest that assessing cervical disability and postural stability should be integral to the geriatric evaluation, as they may identify individuals at higher risk of mobility limitations.